Catalytic abatement of CO species from incomplete combustion of solid fuels used in domestic cooking. Issue 8 (August 2018) - Obada, D.O.; Peter, M.; Kulla, D.M.; Omisanya, N.O.; Atta, A.Y.; Dodoo-Arhin, D.
Abstract: This study reveals a first time approach to catalytic based interventions primarily on indoor air pollution emanating from commercial and household solid fuel burning in a region in Nigeria. An intensive survey of the temperatures at different locations in the common stoves used for cooking was conducted so as to ascertain temperatures suitable for catalyst efficiency and stability. Furthermore, cobalt and iron based catalysts were prepared using ultra stable Y type zeolite as supports. The synthesized catalysts were characterized for its physico-chemical properties. The catalytic efficiency of the supported catalysts was tested using simulated exhaust gases in a fix bed reactor. The study further explored real time testing of the catalyzed ceramic monolith using two different wood species. First, the best catalyst in terms of simulated exhaust testing was selected. Consequently, a small layer of zeolite Y was deposited at 3% of the monolith weight to enhance the subsequent adhesion of the best catalyst powder to the structured monolith. Then to catalyze the zeolite Y wash-coated monolith with the cobalt precursor, the dip coating technique was used. From the results, the average values of temperatures observed from the surveyed cook stoves using wood and plant residue as fuel were confirmed to be in the range of 203–425 °C which is considered suitable for catalysts activity. The Co/ZY catalyst showed approximately 100% CO conversion (T100 ) at 250 °C for initial CO concentration of 1000 ppm, making it the most effective, while T100 was increased to 275 °C and 325 °C for Fe/ZY and Co-Fe/ZY catalyst respectively at an exhaust residence time of 20000 h −1 . The catalytic converter in real time testing for CO abatement performed well for both wood species. Only minor differences have been noticed.